Bewegungsreichweite, Zugkraft und Muskelaktivität bei eigen- bzw. fremdregulierter Dehnung - Glück, S.; Schwarz, M.; Hoffmann, U.; Wydra, G. (Deutsche Zeitschrift für Sportmedizin, 2002)
Ambiguities in terminology have existed in the execution of stretching exercises regarding the definition of active and passive stretching on the one hand, while on the other, action-theoretical considerations were neglected. Therefore, a suggestion is made for restructuring. Additionally, a check will be made whether there are differences between three stretching concepts (direct and indirect self-stretching and indirect external- stretching). The parameters utmost range of motion (BR max ), traction force at constant angle (ZK), greatest tolerated traction force (ZK max ) and muscle activity of the M. biceps femoris (%iEMG biz ) are recorded. 27 sport students (m=26, f=11); 25±2 years; 68±10 kg, 176±9 cm) were randomly divided into three groups and completed three standardized test types each. Test 1: Direct self-stretching (DE) by independent stretching using a rope; Test 2: indirect self-stretching (lE) in which the test person controlled a motor and Test 3: indirect external-stretching (IF), in which the examiner operated the motor. On average, BR max , was 5% higher in DE than in IE or IF. There were no significant differences between the other parameters. In DE, BR max , was highly-significantly higher than in the indirect procedures. From a sensomotor action regulation point of view, direct self-stretching appears more favorable on the basis of the data recorded. The new structure is clearer and easier in practical applications. Ambiguities in terminology are avoided.